Analyzing EEG patterns in young adults exposed to different acrophobia levels: a VR study - Russo, Samuele; Tibermacine, Imad Eddine; Tibermacine, Ahmed; Chebana, Dounia; Nahili, Abdelhakim; Starczewscki, Janusz; Napoli, Christian (Frontiers in Human Neuroscience, 2024)
1) Background:The primary objective of this research is to examine acrophobia, a widely prevalent and highly severe phobia characterised by an overwhelming dread of heights, which has a substantial impact on a significant proportion of individuals worldwide. The objective of our study was to develop a real-time and precise instrument for evaluating levels of acrophobia by utilising electroencephalogram (EEG) signals.(2) Methods:EEG data was gathered from a sample of 18 individuals diagnosed with acrophobia. Subsequently, a range of classifiers, namely Support Vector Classifier (SVC), K-nearest Neighbours (KNN), Random Forest (RF), Decision Tree (DT), Adaboost, Linear Discriminant Analysis (LDA), Convolutional Neural Network (CNN), and Artificial Neural Network (ANN), were employed in the analysis. These methodologies encompass both machine learning (ML) and deep learning (DL) techniques. (3) Results: The Convolutional Neural Network (CNN) and Artificial Neural Network (ANN) models demonstrated notable efficacy. The convolutional neural network (CNN) model demonstrated a training accuracy of 96% and a testing accuracy of 99%, whereas the artificial neural network (ANN) model attained a training accuracy of 96% and a testing accuracy of 97%. The findings of this study highlight the effectiveness of the proposed methodology in accurately categorising realtime degrees of acrophobia using EEG data. Further investigation using correlation matrices for 1 Russo et al.each level of acrophobia showed substantial EEG frequency band connections. Beta and Gamma mean values correlated strongly, suggesting cognitive arousal and acrophobic involvement could synchronise activity. Beta and Gamma activity correlated strongly with acrophobia, especially at higher levels.(4) Conclusions: The results underscore the promise of this innovative approach as a dependable and sophisticated method for evaluating acrophobia. This methodology has the potential to make a substantial contribution towards the comprehension and assessment of acrophobia, hence facilitating the development of more individualised and efficacious therapeutic interventions.